Evaluation of a platelet lysate bilayered system for periodontal regeneration in a rat intrabony three-wall periodontal defect - Babo, Pedro Miguel Sousa (2018)
With currently available therapies, full regeneration of lost periodontal tissues after periodontitis cannot be achieved. In this study, a combined compartmentalized system was tested, composed of (a) a platelet lysate (PL)-based construct, which was placed along the root aiming to regenerate the root cementum and periodontal ligament, and (b) a calcium phosphate cement composite incorporated with hyaluronic acid microspheres loaded with PL, aiming to promote the regeneration of alveolar bone. This bilayered system was assessed in a 3-wall periodontal defect in Wistar rats. The periodontal healing and the inflammatory response of the materials were scored for a period up to 6weeks after implantation. Furthermore, histomorphometrical measurements were performed to assess the epithelial downgrowth, the formation of alveolar bone, and the formation of new connective tissue attachment. Our data showed that the stabilization of platelet-origin proteins on the root surface increased the overall periodontal healing score and restricted the formation of long epithelial junctions. Nevertheless, the faster degradation of the cement component with incorporated hyaluronic acid microspheres compromised the stability of the system, which hampered the periodontal regeneration. Overall, in this work, we proved the positive therapeutic effect of the immobilization of a PL-based construct over the root surface in a combined compartmentalized system to assist predictable healing of functional periodontium. Therefore, after optimization of the hard tissue analogue, the system should be further elaborated in (pre)clinical validation studies.